THE EFFECT OF JOB TRAINING AND REWARDS ON EMPLOYEE PERFORMANCE OF PT BENING'S PRATAMA GROUP (BENING'S CLINIC) BANDUNG BRANCH - Oktavia, Cindy; Yatmikasari, Dyah; Aldira, Thania; Putri, Gina Rizkya Nurmaulida; Ikhsan, Muhammad; M, Sari Dewi Oktari S.E., M. (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aimed to determine the effect of job training and rewards on employee performance at PT. Bening's Pratama Group (Bening's Clinic) Bandung Branch. This research is quantitative. The population in this study amounted to 30 respondents who were all employees of PT. Bening's Pratama Group (Bening's Clinic) Bandung Branch. The data analysis method used in this research is multiple linear regression analysis. The results of the study stated that Job Training (X1) and Rewards (X2) affected the performance of employees (Y) of PT. Bening's Pratama Group (Bening's Clinic) Bandung Branch with an Fcount of 12.869 > Ftable 3.34 (df = n-k-1). In addition, the significant result is 0.000 < 0.05. The effect of the correlation coefficient obtained between job training (X1) and reward (X2) on employee performance (Y) PT. Bening's Pratama Group (Bening's Clinic) Bandung branch is 0.699 with a strong relationship interpretation.